Reproductive Performance Following Transcervical Insemination with Frozen Thawed Semen in Ewes Submitted to Surgical Incision of Cervical Folds (SICF): Comparison with Laparoscopic Artificial Insemination - Pau, Salvatore (Animals (Basel), 2020)
SIMPLE SUMMARY: The anatomical barriers of the female reproductive tract and the low quality of the frozen thawed semen of rams are limiting factors in spreading superior genotypes in the ovine species. Artificial insemination (AI) is therefore mostly performed by laparoscopy. The surgical incision of cervical folds (SICF) has been demonstrated to allow transcervical intrauterine semen deposition. Here we present data regarding pregnancy (PR) and lambing (LR) rates obtained by transcervical AI following SICF, compared to those obtained by laparoscopic AI using frozen thawed semen. The results showed that in 89.7% of ewes submitted to SICF intrauterine, the deposition of semen was allowed. Moreover, in both experimental groups, the PR and LR were similar. These observations suggest that SICF could represent a valid preliminary procedure to allow transcervical AI in animals of superior genotypes contributing to genetic improvement. ABSTRACT: Transcervical artificial insemination (AI) after the surgical incision of cervical folds (SICF) could represent a valid alternative to laparoscopic AI when frozen thawed semen is used. The aim of this experiment was to compare pregnancy (PR) and lambing rates (LR) of ewes submitted either to transcervical AI after SICF or to laparoscopic AI using frozen thawed semen. Pregnant at term ewes (n = 80) were allocated in two experimental groups. After lambing, one group (n = 39) was submitted to SICF. The remaining ewes that were regularly lambed were allocated to the group of laparoscopic AI (n = 40). Six months later, oestrous cycle of both experimental groups was synchronised and all ewes were artificially inseminated with frozen thawed semen. Ewes submitted to SICF underwent transcervical insemination and intrauterine deposition of semen was recorded. The remaining animals were submitted to laparoscopic AI. Pregnancy and LR were recorded. Intrauterine deposition of semen was possible in 89.7% pf ewes submitted to SICF. This group showed similar PR and LR compared to the laparoscopic group (respectively: PR, 71.8% vs. 70% and LR, 64.1% vs. 65%; p > 0.05). Transcervical AI after SICF may represent a valid alternative to laparoscopy in AI protocols requiring the use of frozen thawed semen.